Fabrication of ZnO-RGO nanorods by electrospinning assisted hydrothermal method with enhanced photocatalytic activity - Ramos P.G. (2019)
This work was supported by the Projects Nº 133-FINCYT-IB-2015 and Nº 113-INNOVATE PERU-ISASS-2018, P. R. would like to thank the Peruvian Council for Science and Technology (CONCYTEC) for the Scholarship.